A multicenter, randomized, controlled, single‐blind comparison phase III study to determine the efficacy and safety of gadobutrol 1.0 M versus gadopentetate dimeglumine following single injection in patients referred for contrast‐enhanced MRI of the body regions or extremities. Issue 2 (1st April 2014) - Kuwatsuru, Ryohei; Takahashi, Satoru; Umeoka, Shigeaki; Sugihara, Ryo; Zeng, Mengsu; Huan, Yi; Peng, Weijun; Ma, Lin; Guo, Liang; Teng, Gaojun; Yao, Weiwu; Tozaki, Mitsuhiro; et al.
<x xml:space="preserve">Abstract</x> Purpose To demonstrate the noninferiority of gadobutrol‐enhanced magnetic resonance imaging (MRI) compared with gadopentetate dimeglumine‐enhanced MRI in Asian patients referred for contrast‐enhanced imaging of the body or extremities. Materials and Methods A multicenter, parallel‐group comparison study of Asian adults referred for contrast‐enhanced MRI were randomized (1:1) to either gadobutrol or gadopentetate dimeglumine. Lesions were assessed for three primary visualization variables: degree of contrast enhancement, border delineation, and internal morphology. Secondary efficacy variables included number of lesions detected, match of MRI diagnosis with final clinical diagnosis, and sensitivity and specificity for malignant lesion detection. Safety was monitored for 24 ± 4 hours after contrast agent administration. Results A total of 363 patients received either gadobutrol (n = 168) or gadopentetate dimeglumine (n = 178). Mean total scores for three primary visualization variables were 9.39 and 9.34 for gadobutrol and gadopentetate dimeglumine, respectively. The proportion of patients with matched MRI and final diagnosis and sensitivity for malignant lesion detection was greater for unenhanced versus combined images (gadobutrol: 72.2% vs. 81.7%; gadopentetate dimeglumine: 76.2% vs. 82.2%, respectively). Both contrast agents were well tolerated. Conclusion Gadobutrol (0.1 mmol/kg BW) was well tolerated and effective in Asian patients referred for contrast‐enhanced MRI of the body or extremities. J. Magn. Reson. Imaging 2014. © 2014 Wiley Periodicals, Inc. J. Magn. Reson. Imaging 2015;41:404–413.© 2013 Wiley Periodicals, Inc.